Optimal Design of Novel Microemulsions-Based Two-Layered Dissolving Microneedles for Delivering Fluconazole in Treatment of Fungal Eye Infection - Phuvamin Suriyaamporn; Praneet Opanasopit; Worranan Rangsimawong; Tanasait Ngawhirunpat (Pharmaceutics, 2022)
The optimal design of novel microneedles (MNs) for the ocular delivery system is necessary and useful for improving the effectiveness of medication. The objective of this study was to design and develop the optimal fluconazole (FLUZ)-microemulsions (MEs)-loaded two-layered dissolving MNs as a potential treatment for fungal eye infection. The experimental designs using the simplex-lattice design were used to select the optimal formulation. The two-layered dissolving MNs were fabricated from 3% chitosan and 20% polyvinyl alcohol (PVA) in a weight ratio of 1:4 as an outer layer and FLUZ-loaded MEs containing eugenol, tween 80, PEG400, and water as an inner layer. The physical appearance, mechanical properties, penetration ability, dissolution time, in vitro/ex vivo ocular drug delivery, and antifungal activity were evaluated. From the results, the optimal two-layered dissolving MNs exhibited good physical properties, complete insertion, minimally invasive ocular tissue, and high stability at 4 °C and 25 °C for 3 months. Moreover, the optimal two-layered dissolving MNs showed significantly higher FLUZ permeation into the ocular tissue than other formulations, while providing highly potential antifungal activity. In conclusion, the optimal MEs-loaded two-layered MNs’ formulation had appropriate properties for ocular delivery of FLUZ, resulting in an improvement of fungal keratitis treatment.